(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the interval oscillation for nonlinear neutral impulsive differential equations. Sufficient condition for the interval oscillation of the equations is obtained by using Riccati transformation and estimating the ratio of unknown functions y(t − σ(t)) and y(t). Some known results are generalized and improved. An example is given to illustrate the results.